Intensive insulin therapy in the ICU: the use of computer algorithms. - Mraz M; Kopecky P; Haluzik M (British Journal of Intensive Care)
Elevated blood glucose levels are common in critically ill patients regardless of previous history of diabetes mellitus. Recent studies have shown that tight glucose control by intensive intravenous insulin therapy can markedly reduce the mortality and the occurrence of complications in most of the patient groups. On the other hand, tight glucose control is more labour intensive than traditional approaches and it also significantly increases the occurrence of hypoglycaemia. Clear and easy-to-use algorithms for insulin administration represent a necessary prerequisite for a successful implementation of tight glucose control in standard clinical practice. Computer-based glucose control algorithms appear to carry additional advantages compared to traditional paper-based protocols owing to their ability to adapt to changes in carbohydrate input and insulin resistance resulting in a lower occurrence of human errors and hypoglycaemia. The aim of this review is to summarise currently available algorithms for glucose control in critically ill patients with special attention to computer-based algorithms.